Akuntabilitas Publik Bantuan Operasional Sekolah (BOS ) di SD Negeri No. 060958 Belawan - Syerly Syerly; R. Hamdani Harahap; E. Harso Kardhinata (Jurnal Administrasi Publik (Public Administration Journal), 2018)
Implementation of School Operational Assistance Program (BOS) aims to raise the cost of education for underprivileged students and lighten up for the students in the future, in order to obtain quality basic education services in the implementation of various obstacles both in terms of institutional and technical aspects of operations. One of the schools that received attention and School Operational Assistance (BOS) was the State Elementary School No. 060958 Belawan. Based on the results of the study can be concluded that the Implementation of Accountability in the Management of BOS funds in SD Negeri. 060958 Belawan seen from the aspect of the decision making process made in writing, the existence of Accuracy and completeness of information related to the management of BOS funds, the existence of Clarity of policy goals, and The existence of feasibility and consistency in financial reporting in general has been running well. Aspect of Accountability in Management of BOS in State Elementary School. 060958 Belawan not yet effective in pelaksnaannya is disseminating information about the management of BOS funds, public access to information on BOS fund management activities, management information system and monitoring of results and annual report..